Representations of Cold in the Folklore Picture of World of Yakuts - A. A. Kuzmina (Научный диалог, 2020)
The idea of cold, reflected in the folklore picture of the world of the Yakuts is discussed in the article. The relevance of the work is due to the increased interest in the northern (Arctic) topic, in particular, to the issue of perception of cold by indigenous peoples, which has its own characteristics, ancient and late strata. The novelty of the study lies in the fact that for the first time folklore material is more widely covered, a comparison is made with the features of the perception of cold by other peoples; modern transformations are revealed. The author of the article uses texts of different folklore genres as a material for study: epics, legends, mythological stories, folk songs, tales, proverbs and sayings. The semantics of the word tymny (cold), which has figurative meanings with a negative connotation, is described. It was revealed that in the folklore picture of the world of the Yakuts, the cold is represented in the images of Winter and North, the mythological Bull of Winter, the Lower World inhabited by the abaasy monsters, the Aam-Daan cold, astral objects (constellations, planets). It is reported that folklore reflects not only the negative attitude of the Yakuts to cold, but also the ways of their adaptation to harsh climatic conditions. It is established that at present the idea of cold has undergone a transformation, in particular, it has begun to be perceived positively, which is largely due to the influence of modern mass culture, universal literacy, and improvement of living conditions.